Crash profits : - Weiss, Martin D. (Wiley, 2003)
In Crash Profits, Dr. Weiss weaves a compelling story of Wall Street’s deceit, crimes, and blunders that gave birth to today’s treacherous investing environment. His story then crosses into the future, painting a vivid and alarming picture of the potential damage these misdeeds and mistakes could continue to cause for your stock, bond, and real estate investments in the months ahead. Best of all, Dr. Weiss gives you easy-to-follow, step-by-step instructions to make PROFITS–both while the market is falling and when it recovers.